ENGARUH SOSIALISASI KELUARGA TERHADAP PERKEMBANGAN PRILAKU ANAK (Studi Kasus: Jorong Lubuak Aluang Kecamatan Ampek Nagari Kabupaten Agam) - Warni, Cinto; Melia, Yenni; Elvawati, Elvawati (Pendidikan Sosiologi, 2013)
FamilyÂ  isÂ  theÂ  firstÂ  socializationÂ  agentÂ  inÂ  society,Â  becauseÂ  theÂ  firstÂ  time childÂ  knowsÂ  aboutÂ  valueÂ  andÂ  norm.Â  TheÂ  parentÂ  isÂ  anÂ  essentialÂ  roleÂ  inÂ  formative childÂ  behaviorÂ  developing.Â  TheÂ  processÂ  socializationÂ  thatÂ  doesnâtÂ  byÂ  parentsÂ  is communicationÂ  andÂ  attention.Â  InÂ  thisÂ  researchÂ  analyzedÂ  theÂ  effectÂ  ofÂ  family socializationÂ  inÂ  childÂ  behaviorÂ  developingÂ  inÂ  JorongÂ  LubuakÂ  aluang.Â  InÂ  the background of this research there is some of family that doesnât liabilities as first socializationÂ  agent.Â  OneÂ  ofÂ  themÂ  onlyÂ  thinksÂ  aboutÂ  theirÂ  privateÂ  withoutÂ  think about their child. Thus, it can give effect of child behavior. The formulation of the problemÂ  âDoesÂ  familyÂ  socializationÂ  giveÂ  significantÂ  effectÂ  inÂ  childÂ  behavior developingâ.Â  TheÂ  purposeÂ  ofÂ  thisÂ  researchÂ  isÂ  toÂ  describeÂ  familyÂ  socialization influence to child behavior developing.The theory that is utilized in this research is functional Structural (TalcotPerson).Â Â  ObservationalÂ  methodÂ  thatÂ  isÂ  utilizedÂ  isÂ  quantitativeÂ  methodÂ  with descriptiveÂ  approaching.Â  DataÂ  collectingÂ  toolÂ  asÂ  questionnaire.Â  ThisÂ  researchÂ  is done to 50 informen, with aim to describe family socialization influence to child behavior developing in Jorong Lubuak Aluang.Â  ThisÂ  informen consistÂ  ofÂ  50Â  childwith age 10 until 12 years old that is explain through questionnaire. From the research results show that: 1) The parentâs communication with their child is adverse because of 50 person respondent 62 % adverse categories. 2) The parentâs attention with their child is adverse because of 50 person respondent 72 % adverse categories. 3) The family socialization adverse in child behavior of 50Â  personÂ  respondentÂ  54Â  adverseÂ  categories.Â  4)Â  ChildÂ  behaviorÂ  CausesÂ  justÂ  fine looked of 50 respondent 60% just fine categories. Based on the result research, thereÂ  isÂ  familyÂ  socializationÂ  influenceÂ  toÂ  childÂ  behaviorÂ  developingÂ  inÂ  Jorong Lubuak Aluang. It visually of 50 respondents 62% for adverse.